2022
DOI: 10.1021/acs.chemrestox.2c00041
|View full text |Cite
|
Sign up to set email alerts
|

Toward Better Characterization of a Free-Base Nicotine Fraction in e-Liquids and Aerosols

Abstract: Given that nicotine salts are a growing market, methods are needed to characterize nicotine forms in e-cigarette vaping products. By lowering the free-base nicotine fraction (α fb ) in favor of protonated forms, the addition of organic acids to the eliquid mix greatly modulates nicotine pharmacokinetics and improves vapers' craving. This research investigated (1) the performance of pH measurement, liquid−liquid extraction (LLE), and acid/nicotine molar ratio calculation methods for α fb estimation in 6 nicotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
(108 reference statements)
2
8
0
Order By: Relevance
“…All pH measurements were measured in triplicate. Bourgart et al found that a dilution factor from 2 to 200 yielded similar pH measurements . Note that the pH measurement by Harvanko et al of commercial nicotine salts matched the pH measurements in all the formulated nicotine salts in this study, except for LA.…”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…All pH measurements were measured in triplicate. Bourgart et al found that a dilution factor from 2 to 200 yielded similar pH measurements . Note that the pH measurement by Harvanko et al of commercial nicotine salts matched the pH measurements in all the formulated nicotine salts in this study, except for LA.…”
Section: Methodssupporting
confidence: 78%
“…Note that the term “pH” in this work and others should be used for relative comparisons between e-liquids only. Although pH measurements of PG/VG-based e-liquids with a potentiometric probe are stable upon addition of water and provide a good approximation of the acid content in solution, the values obtained may not be an accurate quantification of hydronium ion activity due to the lower water environment in e-liquids, even upon dilution. , Freebase nicotine e-liquids are generally available at a 3–20 mg/mL nicotine concentration. The freebase nicotine e-liquids have a measured pH of generally 9–10 in commercial formulations, but such alkaline nicotine formulations can cause a bitter and harsh sensation in the throat when inhaling the aerosol, which have been reported as unappealing to users. The role of the organic acid is to allow users to vape at higher concentrations of nicotine without compromising taste as well as increasing nicotine delivery deeper into the lungs, resulting in higher overall user satisfaction .…”
Section: Introductionmentioning
confidence: 99%
“…The nicotine concentration in European e-liquids can range from 0 to a maximum of 20 mg/mL as required by the European Tobacco Products Directive [ 8 ]. Finally, nicotine can also exist in a variety of forms depending on its protonation state driven by pH of the solvent and nicotine pKa [ 42 ] and protonated nicotine salts can be generated with a variety of weak organic acids, including benzoic acid, salicylic acid, or lactic acid, among at least six others [ 43 ]. We have previously discussed the consequences of the heterogeneity of devices and e-liquids, which leads to a large number of in vitro studies with different experimental designs and aims, ultimately making consistent comparisons and robust conclusions on the toxicity of e-cigarette aerosols difficult [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that toluene has a tendency to extract acids, particularly benzoic acid, which was identified in the extracted samples. 48 Additionally, toluene has been found to extract flavors and nicotine. 46 , 48 Consequently, this extraction process can lead to a shift in the fb fraction values, thereby elucidating the larger discrepancies observed between the two methods.…”
Section: Discussionmentioning
confidence: 99%